2011
DOI: 10.1002/kin.20580
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the reaction of propylene oxide with chlorine atoms and hydroxy radicals

Abstract: The kinetics and mechanism of gas-phase propylene oxide (PPO) reactions were studied in a 142-L reaction chamber by long-path Fourier transform infrared spectroscopy at atmospheric pressure and 298 K. Rate coefficients for the reaction of PPO with ozone (O 3 ), chlorine atoms (Cl), and hydroxyl radicals (OH) were measured using the relative rate technique. Product yields of acetic acid, acetic formic anhydride, formic acid, and carbon monoxide were determined for the following reactions: PPO with Cl both in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The title reaction, Cl + CH 3 C(O)OCH 3 → HCl + CH 3 C(O)OCH 2 , has been selected in the present study for the following reasons. First, a large number of experimental studies on the kinetics of the Cl + CH 3 C(O)OCH 3 reaction have been reported, and it is well established from product yield analyses that the major reaction channel is H abstraction by Cl occurring almost exclusively at the methoxy (CH 3 O) end (>95%). ,,, In this connection, only this reaction channel needs to be considered. Measured k ’s at the temperature ( T ) of 298 K obtained from these kinetic studies have values ranging from 1.93 ± 0.27 to 2.86 ± 0.35 × 10 –12 cm 3 molecule –1 s –1 (these lower and upper limits are from refs and , respectively; note that the value of 7.0 × 10 –13 cm 3 molecule –1 s –1 quoted in ref , which was supposed to be from ref , is most likely a misquote).…”
Section: Introductionmentioning
confidence: 99%
“…The title reaction, Cl + CH 3 C(O)OCH 3 → HCl + CH 3 C(O)OCH 2 , has been selected in the present study for the following reasons. First, a large number of experimental studies on the kinetics of the Cl + CH 3 C(O)OCH 3 reaction have been reported, and it is well established from product yield analyses that the major reaction channel is H abstraction by Cl occurring almost exclusively at the methoxy (CH 3 O) end (>95%). ,,, In this connection, only this reaction channel needs to be considered. Measured k ’s at the temperature ( T ) of 298 K obtained from these kinetic studies have values ranging from 1.93 ± 0.27 to 2.86 ± 0.35 × 10 –12 cm 3 molecule –1 s –1 (these lower and upper limits are from refs and , respectively; note that the value of 7.0 × 10 –13 cm 3 molecule –1 s –1 quoted in ref , which was supposed to be from ref , is most likely a misquote).…”
Section: Introductionmentioning
confidence: 99%
“…31 Table 2 compares the experimental rate coefficients with the values obtained by a SAR estimation method and those found in the literature for other epoxy compounds. The third column in Table 2 shows the rate coefficient, k SAR , predicted from the structure-reactivity relationship (SAR) method 41 that has been tentatively applied for the epoxides studied by using the factor F(O) = 1.18 42,43 and F(O) = 1.45. 31 This factor corresponds to the calculated influence of the ether group on the rate constant.…”
Section: Resultsmentioning
confidence: 99%
“…Calculated using the SAR estimation of (a) (Kwok and Atkinson, 1995), (b) (Calvert et al, 2011), (c) (Calvert et al, 2015), (d) (Middala et al, 2011), (e) (Jenkin et al, 2018). (Calvert et al, 2015) (Recomended values of the most recent revision of database for the kinetics of the gas-phase atmospheric reactions of organic compounds).…”
Section: Resultsmentioning
confidence: 99%